La autoría y la acreditación de la identidad en los trabajos personales en Educación a Distancia. Una experiencia - Miguel Zapata Ros (Universidad de Murcia, 2004)
How can works and individual learnings be valued in distance learning? And, after all, how can we promote a distance learning student by giving grades and degrees? There is no doubt that a thesis or research piece plus a many-yearlong process of elaboration in which tens or hundreds of messages are written and exchanged between a student and their tutors offer enough validation elements to evaluate if goals have been met. However, there is an extra added issue of vital importance that crops up before a personal piece of work to consider in the end: how do we know if the real author is the one who claims to be so? The same doubt that originated Steiners vignette in the New Yorker1, in which a dog can be seen before a computer keyboard saying, On the Internet, nobody knows youre a dog, is cast again. Undoubtedly, an essential worry for several basic issues underlies this anxiety: Can a learning program be wholly at a distance? What is the academic or professional guarantee given to those degrees? And what is most, which is their social credibility? This paper approaches the problem of authorship and acknowledgement of identity in personal pieces of work done in distance learning. Besides, this work describes and experience on the area and offers a reflexion on the topic.